THE INFLUENCE OF SERVICE QUALITY AND SWITCHING COST THROUGH CUSTOMER SATISFACTION AND SWITCHING BARRIERS TOWARDS SWITCHING INTENTION TO XIAOMI SMARTPHONE: A Study of Smartphone Users in Malang City - SATYA RASYID TRIABADI (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This research aims at examining the influence of Service Quality and Switching Cost as independent variables through Customer Satisfaction and Switching Barriers as mediating variables towards the Switching Intention to Xiaomi Smartphone as dependent variables. The population of this research is a non-Xiaomi smartphone users in Malang City using quantitative approach employing questionnaire to collect the data. There are 150 questionnaires distributed to every non-Xiaomi smartphone users in Malang City. The collected data were analyzed using quantitative methods with data type of uniform distribution. Purposive sampling were taken as the parameter of this research. The aforementioned variables were analyzed using the Path analysis with a Partial Least Square structural equation modeling based on the software named SmartPLS version 2.0. The results shows that the dependent variable which is the Switching Intention of smartphone users from non-Xiaomi smartphone users is influenced indirectly by Service Quality and Switching Cost as independent variables. The Switching Intention of non-Xiaomi smartphone users also influenced directly and indirectly by the Customer Satisfaction and Switching Barriers as the mediating variables.Keywords:Service Quality, Switching Cost, Customer Satisfaction, Switching Barriers, Switching Intention